Primary Pancreatic Lymphoma: a rare entity in pancreatic mass - Kandel, Noor Dev; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2017)
Primary pancreatic lymphoma is an extremely rare tumor of pancreas which clinico-radiologically mimics with pancreatic adenocarcinoma. The disease is diagnosed often after radical resection of pancreas. We report a case of 63 years old Chinese gentle man with diagnosis of Primary pancreatic lymphoma who was diagnose after surgical resection. Primary pancreatic lymphoma should also be considered as differential diagnosis in pancreatic tumors. There can be some radiological clues but accurate diagnosis depends on histopathological examination. Definitive treatment still remains controversial.